PHYTOCHEMICAL SCREENING OF INFLORESCENCE OF PIPER BETLE - KUMAR, SUSHMA S.; PAULY, SONA V.; G., SOWMYASHREE (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of the current study is to determine the phytoconstituents present in the Inflorescence of Piper betle (IPB). Methods: Phytochemical screening was performed to analyse the phytoconstituents present in IPB and the same was identified by TLC. The phytoconstituents were also estimated quantitatively. Results: Phytochemical screening showed the presence of alkaloids, flavonoids, saponins, tannins and polyphenols. TLC results indicated and confirmed the presence of alkaloids, polyphenols, flavonoids and tannins. On quantification IPB was found to contain 4.2±1.661 mg/ml and 1.523±0.156 mg/ml of flavonoids and tannins respectively. Conclusion: The present study suggests that Inflorescence of Piper betle can be a good source of secondary metabolites.